Evaluation of body esteem and mental health in patients with breast cancer after mastectomy - Mohammad Heidari; Sara Shahbazi; Mansureh Ghodusi (Wolters Kluwer Medknow Publications, 2015)
Introduction: Mastectomy in patients with breast cancer can severely affect their body esteem. It also changes the emotions and attitudes of patients toward their body and causes psychological reactions such as depression, anxiety, and stress. Aims: This study was conducted with the aim of assessing correlation between body esteem and mental health in patients with breast cancer after mastectomy. Materials and Methods: This study is a descriptive study. One hundred patients with breast cancer after mastectomy were selected by convenience sampling from Seyed Al Shohada Hospital in Isfahan. Data gathering tools were questionnaires of body esteem and SCL-25 mental health and were analyzed by SPSS-PC (v.17). Results: According to the score of body esteem (2.80) and the overall average score for body esteem (36.46), patients had low body esteem. About dimensions of the mental health, the highest average was associated with depressive disorders. According to the results of the Spearman correlation coefficient, there was a direct linear relationship between body esteem and mental health. Conclusion: Considering the impact of mastectomy on body esteem and mental health and the relationship between the variables, nurses take steps for identifying and referring patients to the counseling centers to prevent psychological disorder aspects.